PENGGUNAAN INFORMASI AKUNTANSI DAN GENDER PADA KINERJA UKM DENGAN ORIENTASI KEWIRAUSAHAAN SEBAGAI VARIABEL INTERVENING PADA MASA PANDEMI COVID-19 - siti alliyah; Maslichan Maslichan (FE Program Studi Manajemen, 2021)
This research aimed to examine (1) whether the influence of accounting information and gender on SMEs performance, and (2) whether entrepreneurial orientation is capable to mediate the influence of accounting and gender information on SME performance. To achieve these objectives, then conducted survey method, so go directly to the SMEs by dividing the questionnaire.The reliability test results show that each construction has the value of Cronbach's Alpha which is acceptable above 0.70 as the minimum criteria to be acceptable. Based on the result of the validity test indicates that all items of the statement, all other items of the statement are valid because the R count is greater than the R table. Results of data shows that gender has a non significant effect on entrepreneurial orientation of SMEs in Kab. Rembang, the use of accounting information has a significant positive effect on business performance in Kab. Rembang. Gender has a non significant influence on business performance of SMEs. Entrepreneurial orientation has a non significant effect business performance of SMEs in Kab. Rembang. To test Sobel Test shows results that entrepreneurial orientation and gender cannot explain the indirect relationship between the use of accounting information on business performance. Keywords: Keywords: accounting information, gender, SMEs’ performance